Machine Learning and Traditional Statistics Integrative Approaches for Bioinformatics - Diaa, Nabaa Muhammad; Abed, Mohammed Qadoury; Taha, Sarmad Waleed; Ali, Mysoon (Journal of Ecohumanism, 2024)
Background: Bioinformatics, which integrates biological data with computational techniques, has evolved significantly with advancements in machine learning (ML) and traditional statistical methods. ML offers powerful predictive models, while traditional statistics provides foundational insights into data relationships. The integration of these approaches can enhance bioinformatics analyses. Objective: This study explores the synergistic integration of machine learning and traditional statistical techniques in bioinformatics. It aims to evaluate their combined efficacy in enhancing data analysis, improving predictive accuracy, and offering deeper insights into biological datasets. Methods: We utilized a hybrid approach combining ML algorithms, such as support vector machines (SVM) and random forests (RF), with classical statistical methods, including linear regression and principal component analysis (PCA). A dataset comprising 1,200 gene expression profiles from breast cancer patients was analyzed. ML models were evaluated using metrics like accuracy, precision, recall, and F1-score, while statistical techniques assessed data variance and correlation. Results: The integration of ML and traditional statistics resulted in an accuracy improvement of 10% for gene classification tasks, with ML models achieving an average accuracy of 92%, precision of 91%, and recall of 90%. Traditional methods provided critical insights into data variance and inter-variable relationships, with PCA explaining 65% of the data variance. This hybrid approach outperformed standalone methods in both predictive performance and data interpretability. Conclusion: Integrating machine learning with traditional statistics enhances the analytical power in bioinformatics, leading to more accurate predictions and comprehensive data understanding. This combined approach leverages the strengths of both methodologies, proving beneficial for complex biological data analysis and contributing to the advancement of bioinformatics research.